Schools, universities and history in the world of twenty-first century skills: "The end of knowledge as we know it"?. Issue 1 (5th June 2017) - Yates, Lyn
Abstract : Purpose: This paper was originally presented as a keynote presentation to the annual conference of the ANZHES whose theme was "knowledge skills and expertise". The purpose of this paper is to reflect on history as a field of study in the context of changing conditions and new debates about knowledge in the twenty-first century. Design/methodology/approach: The paper reviews three important lines of sociological argument about changed conditions for knowledge: the case to "bring knowledge back in" to school curriculum; the contention that knowledge in universities is moving from "mode 1" to "mode 2" forms; and arguments about testing and audit culture effects on the practices of universities and schools. It then draws on interviews with historians and history teachers to show how they think about the form of their field, its value, and the impact of the changing conditions signalled in those arguments. Findings: The paper argues that some features of the discipline which have been important to history continue to be apparent but are under challenge in the conditions of education institutions today and that there is a disjunction between teachers' views of the value of history and those evident in the public political arena. Research limitations/implications: The paper draws on a major Australia Research Council funded study of "knowledge building across schooling and higher education" which focusses on issues of disciplinarity and the fields of physics and history. Originality/value: The paper is intended as a new reflection on the field of value to those working as historians.